Sustainable strategies for sodium reduction in biltong by improving healthiness without impairing safety - Rita Opperman; Barbara E. van Wyngaard; MacDonald Cluff; Carina Bothma; Eileen Roodt; Celia Hugo; Arno Hugo (South African Journal of Science)
Biltong is a popular South African savoury meat snack, which is preserved by drying and adding vinegar and salt to inhibit microbial growth. It is stable at room temperature and can be considered a safe and sustainable local food system. Unfortunately, biltong has exceptionally high sodium (Na) levels, and there are currently no regulations regarding the Na content of biltong. Therefore, research needs to be conducted to determine the effect of Na reduction or replacement on South African biltong’s shelf life and chemical and sensory properties. In this study, sodium chloride (NaCl) inclusion levels in biltong models were altered to contain normal or 50% reduced NaCl in combination with various salt replacers – potassium chloride (KCl), organic potassium (K) salts and K-lactate – in different treatments. The treatments with the various levels of Na and replacers were evaluated against the positive control, the normal added NaCl levels and the negative control, which contained 50% of the normal NaCl levels. We found that a 50% reduction in NaCl was possible, and there were no serious adverse effects on the product’s chemical, sensory or microbial qualities. The treatments, which contained KCl, organic K salts and K-lactate as replacers, were successful at maintaining the sensory properties of biltong in comparison to the positive control. Overall, the treatment that contained the organic K salts, in conjunction with the K-lactate, was the most effective in inhibiting the growth of Escherichia coli, Staphylococcus aureus and lactic acid bacteria.